Studies of N,N-Dibutyltrimethylenediamine and N, N,N'Triethylenediamine for CO2 absorption and desorption - Mohd Akhir, Ammar; Halim Tan, Yudy; Agar, David W. (Universiti Putra Malaysia Press, 2008)
CO2 gas emissions and their increasing role in global warming have become an issue of much concern. Chemical absorption is preferred for lowering the partial pressure of CO2, The potential of completely new amines N,N-Dibutyltrimethylenediamine and N,N,N' Triethylenediamine which are both categorized and widely known as diamine (amine that may contains two active nitrogen atoms without going through any conventional mixing process) were investigated for CO2 absorption and desorption processes. In order to investigate the potential of these diamines for CO2 absorption and desorption, experiments and analysis were conducted to determine the absorption rate, absorption capacity, desorption rate and desorption effectivity of CO2.